Case report: Unexpected presentation of Wellens’ syndrome in Public Health Centers - Afandy, Jonathan Edbert; Taslim; Putra, Swastya Dwi (Tarumanagara Medical Journal, 2024)
Electrocardiography (ECG) is an essential tool for diagnosing and risk-stratifying acute coronary syndrome patients. Only 20% of acute ischemia ECG changes are recognized by emergency medical service (EMS) providers. Wellens’ syndrome is an ECG characteristic, as certain ST-T segment abnormalities in the setting of impending myocardial infarction (MI) patients suggestively caused by critical stenosis in the proximal left anterior descending (LAD) artery. Myocardial infarction from a culprit lesion in the LAD artery is related to worse clinical outcomes. The first patient was a 27-year-old man smoker who presented with epigastric pain accompanied by shortness of breath in the past 1 hour. His blood pressure was 170/100 mmHg and physical examination revealed epigastric tenderness. ECG revealed biphasic T waves in leads V2-V5, suggestive of Wellens type A. The second patient was a 37-year-old man who presented after being stung by an insect 15 minutes before. Upon observation, the patient suddenly experienced left-sided chest pain accompanied by diaphoresis. ECG revealed inverted T waves in leads V2-V4, suggestive of Wellens type B. Further history-taking revealed that he had experienced this kind of symptoms three months prior and had a history of hypertension, dyslipidemia, and a current smoker. Unfortunately, both patients refused to be referred for further examination and management. Physicians and EMS providers should be aware of Wellen’s syndrome. Misinterpretation of this ECG characteristic could lead to fatal outcomes. Educating patients thoroughly about their condition is also important.